Helicopter modelling and study of the accelerated rotor. (January 2018) - Castillo-Rivera, S.; Tomas-Rodriguez, M.
Highlights: A helicopter dynamic model is modelled to detect vibrations using VehicleSim. The dynamic performance and the control action are embedded in a single code. Some rotor parameters are modified with the purpose of study their impact on the rotorcraft under the action of an accelerated rotor. A tool that allows to predict vibrations on the helicopter. Abstract: This work presents a helicopter dynamic model that captures the fuselage vibrations for an accelerated main rotor. Some rotor parameters are modified with the purpose of study their impact on the rotorcraft. Being this, a tool that allows to predict vibrations on the helicopter. The rotorcraft model has been built up by using VehicleSim, software specialized in modelling mechanical systems composed by rigid bodies. The rotors are articulated, the main rotor takes into account flap, lag and feather degrees of freedom for each of the equispaced blades and their dynamic couplings. The dynamic performance and the control action are embedded in a single code, thereby VehicleSim does not require external connection to other software package. This generates some advantages such as to reduce the compilation time. The control methodology makes use of PID controllers (Proportional, Integral, Derivative), which allows to use VehicleSim commands exclusively. The state space matrices have been obtained in order to analysis the uncoupled main rotor flap and lag modes. The detection of vibrations from the offset flap hinge as well as the lag hinge are not straightforward tasks and this helicopter model provides an accurate tool to study these. A short time Fourier transform processing is used to analysis the vibrations and these have shown to agree with the expected behaviour.